A Universidade Aberta do Brasil na Amazônia: desafios a gestão de um polo de apoio presencial no oeste do Pará - COELHO, Aldilene Lima (Universidade Federal do Oeste do Pará, 2021)
This study presents as a topic the distance education in Higher Education and has the nuclear objective to understand the process of management of EaD polo of the Open University System of Brazil (UAB), with a view to making Higher Education distance in the west of Pará. For this purpose, it was sought: to capture the perception of the coordination of UAB Juruti and UAB coordinations at IES (Federal University of Pará / UFPA) regarding the accomplishment of the objectives proposed by the UAB System; to verify how the managers (coordination of polo and UAB coordinators in the IES) work with the complexities put by the modality of distance learning in the pole studied; to identify the obstacles to the management of a face-to-face support center of the Open University of Brazil, in the interior of the Amazon (Juruti city); and to analyze the managerial processes used by UAB System managers (coordination of UAB coordination and coordination in the IES) when planning and operating the activities in the presence support pole studied. The construction of this research took place through a qualitative (RODRIGUES, 2006), descriptive, case study type study (MINAYO, 2014), assuming bibliographical, documentary and empirical research. The data analysis techniques (YIN, 2005), non-participant observation (VIANNA, 2003) and the questionnaire (OLIVEIRA, 2016) were used to produce the data, organized with the contribution of content analysis (BARDIN, 2011) and interpreted through the triangulation of methods (MINAYO et al, 2005). The construction of the theoretical base was based on Fleury and Ouverney (2007), Belloni (1999), Costa and Pimentel (2009), Nunes (2009), Azevedo (2012), Brasileiro, Colares e Colares (2012), Lucena et al. (2012), Bastos et al. (2013), Castells (2016), among others, dialoguing with the empirical data, the official documents and the legal framework of the study. The results demonstrate that the UAB System has fulfilled its priority objective, that is, the training of primary education teachers at the polo studied, and other poles installed in the State of Pará. Regarding the complexities attributed to the EaD at a pole inside the Amazônia, the coordinators seek to transpose them through dialogue with the actors involved in the process, through solutions that can be creative and innovative, as reported in the body of the text. Among the challenges to polo management are the lack of resources, the high rate of evasion, the lack of qualified personnel to work in the EAD, among others. The strategies for planning and organizing activities between IES and polo are elaborated at a distance, through e-mail, video conferencing, visit in loco; regarding the follow-up of the activities that take place at the polo, the coordinators who work at the IES show that it could be better if the financial resources were not so limited. Thus, it is concluded that, despite the challenges presented to the actors belonging to the UAB in the interior of the Amazon, this network has an effective chance of reaching an expressive number of people, since from the implantation of the EaD the public universities have reached places away from their headquarters, giving the opportunity to students, whether they are professionals of the municipal education network or not, to seek the dreamed academic training, mainly higher education, and as a result of this access to the labor market in their places of origin.